Effects of celastrol on the heart and liver galaninergic system expression in a mouse model of Western-type diet-induced obesity and metabolic dysfunction-associated steatotic liver disease and steatohepatitis - Canová, Nikolina; Šípková, Jana; Arora, Mahak; Pavlíková, Zuzana; Kučera, Tomáš; Šeda, Ondřej; Šopin, Tijana; Vacík, Tomáš; Slanař, Ondřej (Frontiers in Pharmacology, 2025)
BackgroundThe complexity of the galaninergic system is still not fully understood, especially under specific pre-existing comorbidities related to metabolic dysfunction. A plant-derived triterpenoid celastrol was demonstrated to exert a complex effect on the galaninergic system and to have hepatoprotective and anti-obesity properties. However, the exact molecular mechanisms responsible for these effects remain unclear. Specifically, there are no data on the impact of celastrol on the heart and liver galaninergic system. Therefore, this study aimed to investigate the effects of celastrol on the galaninergic system expression in the heart and liver of mice suffering from diet-induced obesity and metabolic dysfunction-associated steatotic liver disease and steatohepatitis (MASLD/MASH).MethodsThe male mice C57BL/6J were fed a Western-type high-fat diet for 16 and 20 weeks to induce obesity and MASLD/MASH. Celastrol was administered along with a specific diet for the last 4 weeks to evaluate its impact on the progression of these conditions. Moreover, the inhibitor of sterol regulatory element-binding protein 1/2 (SREBP1/2), fatostatin, was also tested to compare its influence on the galaninergic system with celastrol.ResultsThe study demonstrates that celastrol treatment was safe and led to a reduction in food and energy intake, body fat and liver weights, and MASLD-to-MASH progression and improved glucose tolerance, serum biochemistry markers, and hepatic lipid peroxidation in mice. Quantitative gene expression originally showed significant regulation of galanin and all three of its receptors (GalR1/2/3) in the heart ventricles and only GalR2 in the liver of obese mice. Celastrol influenced the gene expression of galanin receptors: it downregulated Galr1 in the heart and upregulated Galr2 in the liver and Galr3 in the heart ventricles, potentially affecting energy metabolism, oxidative stress, and inflammation. Fatostatin suppressed gene expression of all the detected members of the galaninergic system in the heart ventricles, depicting the role of SREBP in this process.ConclusionThese findings suggest that celastrol may beneficially modulate the galaninergic system under obesity and MASLD-to-MASH progression, indicating its potential as a therapeutic agent for disorders associated with metabolic dysfunction.